Antihepatotoxic effect of ethanolic extract of Pellionia heyneana Wedd., leaf on paracetamol induced liver damage in Wistar rats - V Vilash; P G Latha; A L Aneeshkumar; Ragesh R Nair; S Rajasekharan (Journal of Traditional and Folk Practices (JTFP), 2016)
Pellionia heyneana Wedd. leaf has been used by the Cholanaikan tribe as traditional medicine to enhance general health, immunity and also to treat various liver ailments. However, no scientific reports are available regarding its traditional claim. In the present study, scientific evaluation of antihepatotoxic activity of P. heyneana crude ethanolic leaf extract (PHLE) was carried out on paracetamol induced liver damage in Wistar rats. The substantially altered serum parameters were restored towards normalization significantly by the plant extract. The biochemical observations were supplemented with histopathological examinations of liver samples. All these results are comparable with the known hepatoprotective agent, silymarin.